The Effect of Alpha-Amylase Types and Time of Enzyme Activation Towards the Sensory and Physicochemical Properties of Oat Milk - Pek, Maria Priska Angelina; Dewi, Desak Putu Ariska Pradnya (Universitas Bio Scientia Internasional Indonesia, 2025)
Plant-based or non-dairy milk substitutes are becoming favored in the growing field of functional beverages driven by factors such as health benefits, allergies, lactose intolerance, and the rise in vegan diets. However, there are challenges to producing oat milk, such as achieving the desirable texture and taste. This study is aimed to have 4 treatments utilizing 2 different kinds of amylase (Amylase 1 and Amylase 2) along with 2 different times of enzymatic activation (20 minutes and 30 minutes) to modify physicochemical properties and sensory qualities. This process includes the utilization of 2 amylase enzyme brands, guar gum, canola oil, and oat flour which improves the overall quality of this alternative to dairy milk. Oat milk making involves combining water, oat flour, and oil. The mixture was then processed until smooth before filtration and amylase was added for an enzymatic reaction. The mixture was then pasteurized, and finally, guar gum solution was stirred in before serving. This research investigates the physicochemical characteristics and sensory qualities of enzymatic oat milk, encompassing pH, brix, stability, viscosity, 5-point hedonic test, and rank test. Moreover, it was found that there are significant differences in all of the attributes including pH, brix, viscosity, and stability with the p-value of less than 0.001. It was also found that the time of enzymatic activation had no impact towards the physicochemical and sensorial properties of oat milk. Lastly, sensorial properties of the oat milk prepared with amylase enzymes scored higher in all attributes compared to the negative control. Keywords: Oat milk, amylase, activation time, sensory, physicochemical